Nilai-Nilai Pendidikan Islam Dalam Tradisi Batamat Al Qur’an - Ziyadatul Husna; Ali Muammar (CV. ITTC INDONESIA, 2026)
The Batamat al-Qur’an tradition in Banjar society represents the acculturation of Islam with local culture, embedding profound educational values. The central issue addressed in this study is how Batamat functions both as a religious ritual and as a medium for internalizing Islamic values. The research aims to explore its concept, philosophy, identity, and educational significance. A qualitative-descriptive approach was employed, relying on literature review, document analysis, and historical-cultural studies of Banjar traditions. Findings reveal that Batamat is not merely a Qur’anic completion ceremony but also a means of strengthening tawhid, worship, morality, and social solidarity. The tradition manifests in diverse forms mass Batamat, wedding Batamao, manyaratus, mulutan (Maulid celebration), and Ramadan tadarus each affirming the Qur’an’s role as a guide for life. Ultimately, Batamat serves as a medium for character and spiritual education, fostering discipline, responsibility, gratitude, and communal harmony. This makes Batamat al-Qur’an highly relevant for contextualization within modern Islamic education, bridging cultural heritage with contemporary pedagogical needs.